1998
DOI: 10.1023/b:drem.0000005896.68083.ae
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sleep paralysis among Canadian and Japanese college students.

Abstract: Although sleep paralysis had been treated as one of the symptoms of narcolepsy, recently it has become recognized as occurring frequently in normal individuals. However, among the few published studies that have examined sleep paralysis, there are great discrepancies in its reported prevalence. These discrepancies could be attributed to differences in survey methods, to the description of the symptom employed in each study, or to the race or culture of the research participants. We administered a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 14 publications
(36 reference statements)
4
47
0
7
Order By: Relevance
“…Only 7 percent of the comparison group said ''yes'' to these two questions. The Nelson, Mattingly, Lee, and Schmitt article references indicated a prevalence of sleep-related hallucinations in 19 percent, and specifically falling-asleep hallucinations in 24 to 28 percent, of the general population, figures consistent with our review of other pertinent literature on these topics (Cheyne, Newby-Clark, and Rueffer, 1999;Fukuda, Ogilvie, Chilcott, Vendittelli, and Takeuchi, 1998). The American Psychiatric Association (2000, p. 610) indicated an overall prevalence of 10 to 15 percent.…”
Section: Composition Of Participant Groupssupporting
confidence: 77%
“…Only 7 percent of the comparison group said ''yes'' to these two questions. The Nelson, Mattingly, Lee, and Schmitt article references indicated a prevalence of sleep-related hallucinations in 19 percent, and specifically falling-asleep hallucinations in 24 to 28 percent, of the general population, figures consistent with our review of other pertinent literature on these topics (Cheyne, Newby-Clark, and Rueffer, 1999;Fukuda, Ogilvie, Chilcott, Vendittelli, and Takeuchi, 1998). The American Psychiatric Association (2000, p. 610) indicated an overall prevalence of 10 to 15 percent.…”
Section: Composition Of Participant Groupssupporting
confidence: 77%
“…Fukuda y col ( 12,17 ), Penn y col ( 15 ) y Awadalla y co1 ( l6 ) informan una menor prevalencia (24,5% -28,8%). Esto pudo deberse a las características de nuestra población de estudio, de la connotación cultural dada a esta entidad y del cuestionario usado.…”
Section: Discussionunclassified
“…We do not believe CTS is related to SP; however, research into SP has created some interesting information about sleep position. In one study of sleep positions in Japan and Canada, Fukuda found that 58.8% of Canadian university students and 32.4% of Japanese university students sleep on their side, whereas 40.5% of Japanese and 3.5% of Canadian students sleep on their back [15].…”
Section: Pregnancy and Sleep Positionmentioning
confidence: 99%